RESEARCH OF QUALITY INDICATORS OF FUR PLATES FROM RAG - N.D. Ergasheva; F.U. Nigmatova (Journal of new century innovations, 2023)
Abstract: Much attention is paid to the issues of waste-free use of the area of skins of fur semi-finished products of various types. The share of costs for fur and leather semi-finished products in the cost of fur and leather products reaches 80–90%. Therefore, their economical use plays a very significant role in reducing the cost of products. Increasing the utilization rate of fur semi-finished products and natural leather materials due to the maximum use of the flap and low-grade raw materials plays an important role.